2013
DOI: 10.1155/2013/346067
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Origins of Chronic Renal Disease: An Integrative Hypothesis

Abstract: Cardiovascular diseases are one of the leading causes of mortality. Hypertension (HT) is one of the principal risk factors associated with death. Chronic kidney disease (CKD), which is probably underestimated, increases the risk and the severity of adverse cardiovascular events. It is now recognized that low birth weight is a risk factor for these diseases, and this relationship is amplified by a rapid catch-up growth or overfeeding during infancy or childhood. The pathophysiological and molecular mechanisms i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
3

Year Published

2015
2015
2017
2017

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 157 publications
(165 reference statements)
1
23
0
3
Order By: Relevance
“…These changes are known to increase SNGFR, to affect the glomerular endothelium barrier, to impair endothelium-dependent vasodilatation, and to stimulate the sympathetic nervous activity responsible for HT, one of the leading causes of CKD (28)(29)(30)(31)(32). Even though blood pressure was not monitored in the current study, we hypothesize that such metabolic, hormonal, and vascular changes enhanced the adaptive glomerular hemodynamic changes and renal injury already acquired during the neonatal period and accelerated the occurrence of proteinuria and glomerular sclerosis (33). Further investigation would be needed to confirm this hypothesis.…”
Section: Discussionmentioning
confidence: 79%
“…These changes are known to increase SNGFR, to affect the glomerular endothelium barrier, to impair endothelium-dependent vasodilatation, and to stimulate the sympathetic nervous activity responsible for HT, one of the leading causes of CKD (28)(29)(30)(31)(32). Even though blood pressure was not monitored in the current study, we hypothesize that such metabolic, hormonal, and vascular changes enhanced the adaptive glomerular hemodynamic changes and renal injury already acquired during the neonatal period and accelerated the occurrence of proteinuria and glomerular sclerosis (33). Further investigation would be needed to confirm this hypothesis.…”
Section: Discussionmentioning
confidence: 79%
“…This mechanism is still being discussed and recent experimental studies have failed to show such a link. Boubred et al [23] reported that the reduced nephron number is not sufficient by itself to induce long-term renal diseases, but that it constitutes a factor of vulnerability when additional factors, in particular a rapid postnatal growth or overfeeding, promote the early onset of diseases through a complex combination of various pathophysiological pathways. The authors suggest that future research may aim to clarify early biomarkers of nephron endowment and early renal injury in order to determine optimal perinatal nutrition and eventual prophylactic measures to be applied to infants at increased risk of developmentally programmed adult diseases [23].…”
Section: Discussionmentioning
confidence: 99%
“…Humans have an average of 1 million nephrons per kidney, but the number varies in individuals from 200 000 to more than 2 million (Bertram et al 2011). A small number of nephrons is associated with increased sensitivity to the development of high blood pressure and chronic kidney disorders in adulthood together with further factors such as rapid postnatal growth or overfeeding during infancy or childhood (Abitbol and Rodriguez 2009;Bertram et al 2011;Boubred et al 2013). In rats, intrauterine growth retardation may induce a reduced number of nephrons at birth, which may not be fully compensated for during the first weeks after birth (Merlet-Bénichou et al 1994).…”
Section: Prenatal and Postnatal Exposure Up To The End Of Lactation Ratsmentioning
confidence: 99%